Analysis Of the Influence of Simulation Training a Level of Development of Practical Skills in The System of Training a Dentist from The Point of View of Students Based on Social Survey - Umarova Odinakhon Numonovna; Rasulova Makhpiratkhon Mehmonkulovna (Genius Journals, 2021)
In the training of future dentists in the field of medicine of the known higher education, the emphasis is on the adequate combination of theoretical knowledge with practical knowledge and skills.
Keywords: Cariesology; phantom; virtual learning; model